The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.36111/jvmohr.2019.1(2).0010
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of pre-clinical and clinical research reports on small ruminants published during the last six decades in the then East Pakistan and in Bangladesh

Abstract: Background: A dozen of veterinary academic institutions offer degree courses with pre-clinical and clinical studies and conduct research works but their activities are not coordinated and unified in Bangladesh. An attempt has been made to review the pre-clinical and clinical research reports in small ruminants which would help the concerned academicians, research scientists and research funded organizations to update their knowledge of specialization and use this reference as a starting point for formulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 278 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Compared to the various types of fractures in this study, transverse fractures were more prevalent in calves (55%, n = 53) and cats (59%, n = 10). These results concur with the findings of [17,18]. Contrary to the results of this study, Minar et al [15] reported a higher incidence of oblique fractures than other types of fractures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to the various types of fractures in this study, transverse fractures were more prevalent in calves (55%, n = 53) and cats (59%, n = 10). These results concur with the findings of [17,18]. Contrary to the results of this study, Minar et al [15] reported a higher incidence of oblique fractures than other types of fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to the results of this study, Minar et al [15] reported a higher incidence of oblique fractures than other types of fractures. Oblique and transverse fractures are more common, which suggests that bending or compression forces are the main forces acting on the long bone [18].…”
Section: Discussionmentioning
confidence: 99%
“…(Sinum et al 2011 and Minar et al 2013) reported a higher incidence of oblique and femoral fractures in calves which suggests that bending or compression forces are the main forces acting on the long bone. (Samad et al 2019). The distal fracture was the most common in long bone fracture (67%) followed by middle and proximal fracture.…”
Section: Etiology Of Fracturesmentioning
confidence: 99%